Tooth Extraction and Bone Drill Hole in Wistar Rats: Kinetics of Biochemical Markers During Wound Healing: Extraction Dentaire et Trou de Forage Osseux Chez les Rats Wistar : Cinétique des Marqueurs Biochimiques Lors de la Cicatrisation - Nkolo Tolo Francis Daniel; Nkeck Jan Rene; Tanetchop Magouo Nelly; Tcheutchoua Yannick Carlos; Mame Momo Edwige Léa; Ama Moor Vicky Jocelyne (HEALTH RESEARCH IN AFRICA, 2024)
ABSTRACT Introduction. Biochemical markers provide a dynamic picture of the bone remodeling process. The aim of this study was to determine the kinetics of remodeling markers during bone healing under two models of induced lesions in the Wistar rat. Methodology. Over a three-month period, from February to April 2024, we conducted an experimental study involving wistar rats weighing a minimum of 150g and aged eight weeks. The animals (N=24) were randomly divided into three groups of eight rats. Group I was the control group. In group II, the rats had undergone dental extraction, while in group III, a bone drill hole was made in the mandibular symphysis. The follow-up period was 45 days. Data analysis was performed using Graph pad sprim software version 8.0.1. l. Results were expressed as mean plus or minus standard error on the mean. Results. We included 24 rats. We observed weight loss in Group II females at weeks 2 and 6. PAL concentrations increased significantly in groups II and III at weeks 4,5,6. On the other hand, we observed a decrease in calcium concentration in female rats of groups II and III at week 4. Conclusion. At week 4 post-operatively, the determination of PAL and/or calcium could provide information on the level of consolidation. RÉSUMÉ Introduction. Les marqueurs biochimiques fournissent une image dynamique du processus de remodelage osseux. Le but de cette étude était de déterminer la cinétique des marqueurs de remodelage lors de la cicatrisation osseuse sous deux modèles de lésions induites chez le rat de wistar. Méthodologie. Nous avons mené sur une durée de trois mois, allant de Février à Avril 2024 une étude expérimentale incluant les rats wistar d’un poids minimal de 150g et d’un âge de huit semaines. Les animaux (N=24), étaient répartis de manière aléatoire en trois groupes de huit rats. Le groupe I représentait le groupe témoin. Dans le groupe II les rats avaient subi une extraction dentaire, tandis que dans le groupe III, un trou de forage osseux était réalisé sur la symphyse mandibulaire. Le suivi s’est fait sur 45 jours. L’analyse des données a été faite avec le logiciel Graph pad sprim version 8.0.1. l. Les résultats ont été exprimés sous forme de moyenne plus ou moins erreur standard sur la moyenne. Résultats. Nous avons inclus 24 rats. Nous avons observé une perte de poids des femelles du groupe ii aux semaines 2 et 6. Les concentrations de pal augmentaient significativement dans les groupes II et III aux semaines 4,5,6. Par contre on observait une diminution de la concentration de calcium chez les rats femelles des groupes II et III à la semaine 4. Conclusion. A la semaine 4 post-opératoire, le dosage de la PAL et/ou du calcium pourrait renseigner sur le niveau consolidation.